Language for Specific Purposes International Seminar, 5th, 13-15 April 2006, Dept. of Modern Languages, UTM, Johor Bahru, Johor, Malaysia - Language for Specific Purposes International Seminar 2006 : Johor Bahru); Universiti Teknologi Malaysia. Department of Modern Languages (Johor Bahru : Department of Modern Languages, UTM, 2006)
Contained 44 work papers for the 5th Specific Purposes International Seminar in Microsoft Word format
Keywords: Language and languages; Linguistics